AB0015 Evaluating The Effect of Anti-TNF, Anti-IL6R and Anti-CTLA4 on ACPA Isotypes in Patients with Rheumatoid Arthritis. (15th July 2016) - Hernandez-Flόrez, D.; del Río, T.; Nieto, J.; Ovalles, J.; Martínez, J.; Serrano, B.; Mata, C.; Gonzalez, C.; Monteagudo, I.; Lopez-Longo, J.; Naredo, E.; Valor, L.
Abstract : Background: B-cell depletion therapy decreases autoantibodies formation as rheumatoid factor and anti–citrullinated protein antibodies (ACPA). Other therapeutic targets (TT) such as anti-TNF (tumor necrosis factor), anti-IL-6R (interleukin-6 receptor) and anti-CTL4A (cytotoxic T-lymphocyte antigen-4) modulate the B-cells proliferation/maturation and indirectly the production of autoantibodies. ACPA titers provide us information about disease activity and may be critical for inducing clinical remission in rheumatoid arthritis (RA) patients. Objectives: To evaluate the impact of the therapeutic targets: anti-TNF; anti-IL6R and anti-CTLA4 on ACPA titers in RA patients. Methods: In this longitudinal study we selected ACPA positive patients naïve to BT (N=27). All patients were assessed at baseline and after 4, 8, 12, 24 and 36 months (m) of treatment initiation. Disease activity was assessed by the 28 joint count-disease activity score (DAS28) according to C-Reactive Protein (CRP). ACPA isotypes (IgG, IgA and IgM) were determined by ELISA (CCP2-plates, Eurodiagnostica, SE). Anti-human antibodies isotype specific were used (Binding Site, UK). Statistical analysis was performed according to TT (anti-TNF, anti-IL6R and anti-CTLA4) and anti-TNF therapies (IFX, ADA, ETN). Results: We found a significant DAS28-CRP decrease in: anti-IL6R (p=0.017, p=0.018, p=0.018, p=0.028, p=0.028) and anti-TNF (p=0.002, p=0.002, p=0.003, p=0.004, p=0.007) groups at 4, 8, 12, 24 and 36m. Evaluating the anti-TNF treatments, we found a significant decrease on DAS28 in ADL at 4 (p=0.046) and ETN groups at 4, 8, 12 and 24m of treatment (p=0.043, p=0.043, p=0.043, p=0.043). Comparing TT, the most outstanding reduction of DAS28 was found in anti-IL6R group compared to anti-CTLA4 group (p=0.017) at 8m, probably due to a greater reduction of CRP in anti-IL6R group (p=0.018). Regarding ACPA isotypes, we only found a significant decrease in IgA-ACPA titers in anti-IL6R group at 4, 8 and 12m of treatment (p=0.012, p=0.036, p=0.046). No changes were found neither in other TT nor in anti-TNF therapies. Comparing TT, we found lower IgG-ACPA titers in anti-CTLA4 group compared to anti-IL6-R group (50.25, 98.2U/ml) at 4m. The highest IgG-ACPA titers were found in anti-IL6R (228.7 U/ml) than anti-TNF (53.7U/ml) and anti-CTLA4 groups (71.7U/ml) (p=0.048, p=0.024) at 24m. For IgM-ACPA, the lowest titers were found in anti-IL6R than anti-CTLA4 at 4 and 12m (4m: 2.988 y 3.093OD;12m: 3.004 y 3.116OD) (p=0.012, p=0.017, p=0.017). Conclusions: Patients treated with anti-IL6R and anti-TNF had the most outstanding reduction of DAS28 at the first 8m of treatment. Regarding ACPA isotypes, IgM-ACPA levels were higher in anti-CTLA4 than anti-IL6R probably due to inhibition of B cells class-switching by anti-IL6R therapy. Those patients treated with anti-IL6R presented a progressive decrease of IgA-ACPA and total IgA, as well as, a higher IgG-ACPA titer at 24m. These results showed that both therapies modulate the B cell maturation/differentiation and ACPA production by different immune-regulation pathways, as well as, the cell-cell interaction process. Our data suggests that B-cells and ACPA isotypes monitoring may be useful to further understand their role in the RA pathogenesis and its association with clinical response to BT. Disclosure of Interest: None declared